Abscopal regression of hepatocellular carcinoma after radiotherapy for bone metastasis. Issue 4 (1st October 1998) - Ohba, K; Omagari, K; Nakamura, T; Ikuno, N; Saeki, S; Matsuo, I; Kinoshita, H; Masuda, J; Hazama, H; Sakamoto, I; Kohno, S
Abstract : Spontaneous regression of hepatocellular carcinoma is a rare phenomenon. Abscopal regression of tumours resulting from the effect of irradiation of a tissue on a remote non-irradiated tissue is also rare. The case of a 76 year old Japanese man with hepatocellular carcinoma that regressed after radiotherapy for thoracic vertebral bone metastasis is described. Serum levels of tumour necrosis factor-α increased after radiotherapy. The findings suggests that such abscopal related regression may be associated with host immune response, involving cytokines such as tumour necrosis factor-α.